Pseudoaneurysm of the Dorsalis Pedis Artery Diagnosed on Point-of-Care Ultrasound - Nathan A. Friedman; Caleb P. Canders; Alan T. Chiem (CINQUILL Medical Publishers Inc., 2021)
A 46-year-old man presented with a painless mass on his dorsal right foot one week after striking it on a door. A traumatic hematoma was suspected, and needle aspiration of the mass is considered. However, point-of-care ultrasound performed by the emergency physician identified a pseudoaneurysm of the dorsalis pedis artery, a rare condition that can occur after minor trauma or iatrogenic intervention. This report demonstrates how point-of-care ultrasound can be used to identify a pseudoaneurysm of the lower extremity, thereby expediting emergency department workup and preventing potentially dangerous diagnostic procedures.